2015
DOI: 10.7600/jpfsm.4.223
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m sestamibi retention in skeletal muscles, a potential indicator of mitochondrial function and anaerobic threshold in patients with type 2 diabetes

Abstract: In this study, we investigated the retention of technetium-99m sestamibi (MIBI), a radiopharmaceutical that accumulates in mitochondria, in patients with type 2 diabetes. We hypothesized that patients with type 2 diabetes had lower MIBI counts in their legs than nondiabetic volunteers, and that these abnormalities reflected a low anaerobic threshold (AT) during cardiopulmonary exercise testing (CPX). Eight non-diabetic volunteers (Group N) and 11 patients with type 2 diabetes (Group D) underwent CPX. Mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Recent genetic research in patients with diabetes revealed a positive correlation between general aerobic capacity and the expression of a coregulated subset of oxidative phosphorylation (OXPHOS) genes (OXPHOS-CR) regulated by PGC-1α, which is positively correlated with general VO 2 34) . Our finding of a lower peak VO 2 in patients with diabetes mellitus may be related to muscle metabolism, as described in previous studies [25][26][27][28][29][30][31][32][33][34] . Endothelial dysfunction in diabetic patients is also one of the causes of impaired exercise tolerance 35) , however, it could not be evaluated in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recent genetic research in patients with diabetes revealed a positive correlation between general aerobic capacity and the expression of a coregulated subset of oxidative phosphorylation (OXPHOS) genes (OXPHOS-CR) regulated by PGC-1α, which is positively correlated with general VO 2 34) . Our finding of a lower peak VO 2 in patients with diabetes mellitus may be related to muscle metabolism, as described in previous studies [25][26][27][28][29][30][31][32][33][34] . Endothelial dysfunction in diabetic patients is also one of the causes of impaired exercise tolerance 35) , however, it could not be evaluated in this study.…”
Section: Discussionsupporting
confidence: 89%
“…These results suggest that the difference of peak VO 2 /SMM might be an effect of skeletal muscle metabolism. Impairment of skeletal muscle metabolism in patients with diabetes [25][26][27][28][29] reduces exercise tolerance due to impairment of carbohydrate metabolism, lipid metabolism 30) , insulin resistance, and insulin sensitivity [31][32][33] . Recent genetic research in patients with diabetes revealed a positive correlation between general aerobic capacity and the expression of a coregulated subset of oxidative phosphorylation (OXPHOS) genes (OXPHOS-CR) regulated by PGC-1α, which is positively correlated with general VO 2 34) .…”
Section: Discussionmentioning
confidence: 99%